Implementasi Data Mining dalam Menganalisis Pola Pembelian Produk Toko Oleh-Oleh Umrah dan Haji - Ahmad Rondy; Jani Kusanti; Agus Rianto (Jurnal Syntax Admiration, 2024)
One of the methods that is often applied in Data Mining technology is the Association Rule Mining technique. The Association Rule Mining method aims to find patterns of relationships between items sold in a database and in the retail business is often referred to as Market Basket Analysis. Market Basket Analysis is an analysis method used to understand consumer behavior by identifying purchase patterns from transaction data, besides that this method can also be useful for maintaining the inventory of goods sold. The research methods used are research design methods, method research questions, data collection tools, data analysis, and data validation. The results obtained from this study are the threshold value used is support ≥ 10% and confidence ≥ 30%. The results of the analysis showed the best rule, namely: "Nuts, Honey → Prayer Rugs" with a confidence value of 59%. This means that consumers who buy Nuts and Honey have a 59% chance that they will also buy a prayer mat. This research contributes to efforts to improve the efficiency of stock management and understand consumer behavior through the analysis of purchasing patterns which is ultimately expected to increase customer satisfaction and store sales